Integrasi Nilai-Nilai Hukum Hindu dalam Pengelolaan Lingkungan Hidup Berkelanjutan - Natalia Susilawati; Ni Wayan Eka Sumartini (Tampung Penyang, 2025)
Environmental issues have become a global concern that demands serious attention, as ecosystem degradation directly affects the sustainability of human life. This article discusses the environmental law values in Hindu teachings as a guide for sustainable utilization of natural resources. Through a literature review of Hindu scriptures such as the Vedas, Bhagavad Gita, Dharmasastra, and the Panaturan of Hindu Kaharingan, it is found that principles such as Rta (cosmic order), Dharma (moral duty), Ahimsa (non-violence), Tat Twam Asi (unity of all beings), and Loka Samgraha (common welfare) contain environmental preservation values that align with the concept of sustainable development. The Tri Hita Karana philosophy serves as an ethical foundation emphasizing harmony between humans, God, and nature. Furthermore, religious rituals such as Tumpek Wariga, Nyepi Segara, Manyanggar, and Mamapas Lewu reflect local wisdom that strengthens ecological awareness among Hindu communities. Based on this analysis, Hindu teachings provide both philosophical and normative foundations that can be integrated into modern environmental law to promote equitable and sustainable natural resource management. Kata Kunci : Hindu enviromental law, Tri Hita Karana, environmental sustainability